Understanding microRNAs in the Context of Infection to Find New Treatments against Human Bacterial Pathogens - Álvaro Mourenza; Blanca Lorente-Torres; Elena Durante; Jesús Llano-Verdeja; Jesús F. Aparicio; Arsenio Fernández-López; José A. Gil; Luis M. Mateos; Michal Letek (MDPI AG, 2022)
The development of RNA-based anti-infectives has gained interest with the successful application of mRNA-based vaccines. Small RNAs are molecules of RNA of <200 nucleotides in length that may control the expression of specific genes. Small RNAs include small interference RNAs (siRNAs), Piwi-interacting RNAs (piRNAs), or microRNAs (miRNAs). Notably, the role of miRNAs on the post-transcriptional regulation of gene expression has been studied in detail in the context of cancer and many other genetic diseases. However, it is also becoming apparent that some human miRNAs possess important antimicrobial roles by silencing host genes essential for the progress of bacterial or viral infections. Therefore, their potential use as novel antimicrobial therapies has gained interest during the last decade. The challenges of the transport and delivery of miRNAs to target cells are important, but recent research with exosomes is overcoming the limitations in RNA-cellular uptake, avoiding their degradation. Therefore, in this review, we have summarised the latest developments in the exosomal delivery of miRNA-based therapies, which may soon be another complementary treatment to pathogen-targeted antibiotics that could help solve the problem caused by multidrug-resistant bacteria.